Consumer Acceptance of Branded Fortified Foods and Beverages in India: Towards a Conceptual Framework - Shamal, S.; Mohan, Bijuna C. (Indian Journal of Marketing, 2019)
Purpose: Consumer response to food products is an extremely complex and rapidly evolving field. The prime purpose of this conceptual paper was to explore the impact of different factors on the consumer acceptance of branded fortified foods and beverages (FFBs) in the Indian food market. Methodology: The study was grounded on extensive review of literature. The study has explored insights on the significant variables which had a substantial contribution towards consumer acceptance of FFBs. Originality: It was identified that a clear dearth of research studies regarding consumer acceptance of FFBs is still missing in India. In the Indian context, the present study is the initial one of its kind and tried to address this research gap and developed a conceptual framework for consumer acceptance of FFBs. Findings: The intense review of literature led the study for identifying the contributing elements on consumer acceptance of FFBs. Accordingly, a unified conceptual framework of consumer acceptance has been proposed for the Indian FFBs market. Limitations: The study is limited to a conceptual understanding of consumer acceptance of branded FFBs in the Indian context. The consumer acceptance model proposed in the study was purely grounded on the review of past literature. Practical Implications: The model developed in the study can be a direction to the fortified food industry to fragment and position their offerings effectively to mould a healthy generation. Future Research Directions: This study discussed the various determinants of consumer acceptance. Empirical research studies are recommended to test and validate the proposed propositions.